Bone tissue regeneration in peri-implantitis: A systematic review of randomized clinical trials - Filipe Castro, MSc; Ahmed Sami Bouzidi; Juliana Campos Hasse Fernandes; Marco C. Bottino; Gustavo Vicentis Oliveira Fernandes, PhD (Elsevier, 2023)
Objectives: The goal of this systematic review was to analyze, in randomized controlled clinical trials (RCTs), regenerative techniques used to treat peri-implantitis (PI). Methods: Three databases (PubMed/Medline, EMBASE, and On-Line Knowledge Library) were accessed, applying the PICO strategy (Population [P], Intervention [I], Comparison [C], and Outcomes [O]), with the following focused questions: (i) "In patients who received regenerative treatments for peri-implantitis (P), is the regenerative surgical treatment (I) clinically effective and predictable compared to non-regenerative (C) to treat PI (O)?"; and (ii) "In patients who received regenerative treatments for peri-implantitis (P), the regenerative approach (I), compared to non-regenerative (C), significantly increase the prognosis and implant survival rate in the mid- and long-term (O)?" The inclusion criteria were RCTs published in English between 2012 and 2022, with at least a one-year follow-up, which applied regenerative techniques to treat peri-implantitis. Cochrane's collaboration tool for assessing the risk of bias was used. Main results: Nine articles were included with 404 patients (225 females and 179 males; mean age of 60.44 years). One study evaluated patients after 48 months and another after 88 months. The techniques and devices used were: (i) implantoplasty with Er:YAG laser, (ii) blood concentrate (growth factors), and (iii) EMD, with no statistically significant outcome. Two studies considered the use of titanium granules with a significant increase in radiographic bone identification, whereas regenerative techniques with bone graft (autogenous, alloplastic, and xenograft) were the majority chosen, associated or not, with a collagen membrane. Xenograft had better results radiographically when compared to the autogenous bone graft and presented better results for bone level. There was an overall decrease in bleeding on probing, independent of the control or test group, and a reduction in pocket depth in the groups analyzed. Titanium granules, EMD, Er:YAG laser, and CGF had non-significant results; better results were observed when using bone grafts. The RoB showed a low risk in four studies (44.44%), three with moderate (33.33%), and two with high risk (22.23%). Conclusion: Surgical regenerative treatment was a predictable option in the management of PI and in improving the clinical parameters of peri-implant tissues in the short term, mainly when using porous titanium granules, alloplastic bone grafts, and xenografts.